Psychoeducation on Emotional Regulation to Reduce Aggressive Behavior in Students of High School "X", East Java - Yan Tamara Rosyida; Amherstia Pasca Rina (Journal of Scientific Research, Education, and Technology (JSRET), 2026)
Adolescence is a crucial transition period in human development, where individuals are between childhood and adulthood. During this period, adolescents experience significant changes that can be characterized by various striking changes, both in physical, cognitive, emotional, and psychological aspects, as well as in social relationships. These changes can give rise to negative behavior and violate the law or social norms if not properly addressed, such as aggressive behavior. Aggressive behavior refers to actions intentionally carried out to harm others, such as hitting, kicking, pushing. At High School "X" East Java aggressive behavior among students has become a serious concern that is growing, especially after a complaint from one of the parents revealed an increase in cases of fights between students. Therefore, the main objective of this study is to provide students with a deeper understanding of how to overcome aggressive behavior. The methods used in this study include psychoeducation and role-play. The results of the analysis showed a mean value of the pretest of .00 and a mean value of the posttest of 8.00. The significance value (2-tailed) of the pretest and posttest was 0.001 <0.05, which means there is a significant difference between before and after.